A new installation technology of large diameter deeply-buried caissons: Practical application and observed performance. (July 2022) - Lai, Fengwen; Liu, Songyu; Li, Yaoliang; Sun, Yanxiao
Highlights: A newly developed installation technology of LDDB caissons is reported. Twin LDDB caissons are installed in undrained ground with stiff clays using new technology. Field performance of twin caissons is monitored in real-time. Installation effects and interaction of twin caissons are comprehensively assessed. Abstract: The development of installation technologies of open caissons has been lagging behind increasingly complex construction conditions. For such purpose, a new installation technology of large diameter deeply-buried (LDDB) open caissons has been developed and then used for construction of twin LDDB caissons into undrained ground with stiff soils in Zhenjiang, China. To assess the installation effects and filed performance, a monitoring program was presented to document the variations in total jacking forces provided by new shaft driven method, ground water level (GWL) around the caisson shaft, inclination angles of caisson shafts and radial displacements of surrounding soils as well as surface settlements of existing nearby facilities. It is observed that the monitoring data during the installation falls almost entirely within the design criteria, the reported new technology has limited impacts on the induced ground movements, depending on the variation in GWL, interaction between twin caissons and excavation-induced unloading effect. Moreover, the total jacking forces increase approximately in stepwise shape as the installation depth increases; the change law of surface settlements is highly similar to those of GWL, showing their close correlation; the larger inclination angles of caisson shafts are mainly encountered in the earlier installation phase, but well controllable. Further discussion on ground movements caused by various technologies confirms the feasibility of new installation technology. Both the observed and compared results give greater confidence on the use of such the technology in practice.